Cloud-based assessment of aerosol dynamics and population exposure in Southeast Asia using MERRA-2 and AERONET integration - Zheng, Zhi; Mohd Shafri, Helmi Zulhaidi; Wei, Dong; Jia, Pengfei; Yu, Shengrui; Zhu, Kailin; Mohamed Shariff, Abdul Rashid (Elsevier, 2026)
Southeast Asia exhibits strong spatiotemporal heterogeneity in aerosol loading due to mixed emission sources and monsoon–land–sea circulations, and its interannual variability is strongly modulated by the El Niño–Southern Oscillation (ENSO). This study evaluates the applicability of the Modern Era Retrospective Analysis for Research and Applications, Version 2 (MERRA-2) aerosol products in Southeast Asia during 2015–2024 by integrating AERONET ground-based observations, MERRA-2 reanalysis data, and GHSL population grids within a cloud-based workflow. Hourly MERRA-2 AOD at 550 nm and Ångström exponent were validated against observations from 26 AERONET stations. The results show pronounced site-dependent performance, with stronger agreement over inland sites and degraded skill over coastal and marine-influenced environments. A segmented analysis further reveals a clear loading-dependent bias pattern: MERRA-2 shows a weak positive bias under clean conditions (AOD <0.2) but shifts to systematic underestimation as aerosol loading increases, reaching a pronounced negative bias under heavy loading (AOD >0.6), particularly at coastal stations. Component-resolved analyses indicate that organic carbon and sulfate are the dominant contributors to regional AOD, and ENSO-year contrasts show increased organic carbon contributions relative to normal years. Population-weighted AOD maps reveal persistent exposure hotspots over the Indochina Peninsula and major urbanized corridors, with peak exposure years aligned with El Niño episodes. A process-oriented assessment using regional fire density and precipitation time series further supports that El Niño periods are associated with enhanced fire activity and suppressed precipitation, providing a physically consistent interpretation for ENSO-related AOD anomalies in Southeast Asia.